ANALYSIS OF METHODS FOR DETERMINATION OF CHLORINE DIOXIDE, CHLORITE AND CHLORATE ANIONS IN DRINKING WATER - MOKIIЕNKO Andrii; SPASONOVA, Larysa; BONDARCНUK Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The analysis shows that the primary measure for the purification of drinking water is its reliable disinfection with oxidants, which are chlorine and its compounds, chlorine dioxide, ozone. The aim of the article is to analyze the existing methods for determination of chlorine dioxide, chlorite, hypochlorite and chlorate anions in drinking water. To analyze the chlorine dioxide strength solutions (to control the generator performance) the iodometric method (determination of chlorine dioxide concentration, concentration of free chlorine, chlorite and chlorate anions; relative error ≤ 5%) and the method of direct absorption at 445 nm (determination of chlorine dioxide concentration in the range of concentrations of 100-700 mg / l; relative error ≤ 2%) were used. To analyze the residual concentrations of chlorine dioxide, chlorite and hypochlorite anions in their joint presence the titrimetric and photometric methods with N,N-діетил-1,4-фенилендіамінсульфатом (DFD) (error of determination is of 0.05 mg/l) were used as well as iodometric method with photometric determination of iodine at 350 nm in the concentration range 0.01-0.5 mg/l. To analyze the residual concentrations of chlorine dioxide (selective methods), such methods were used: the photometric method with chlorophenol red in the concentration range of 0.02-0.7 mg/l; relative error ≤ 5%; photometric method with chromic violet acid in the concentration range of 0.1-1.5 mg/l. The method of ion chromatography was used to analyze the residual concentrations of chlorite and chlorate anions. Given the necessity for harmonization of domestic regulatory and guidance documentation with European one, it should be considered as necessary to control chlorites and chlorates in drinking water by method of ion chromatography. It is appropriate to conduct research on the approbation of ion chromatography method for the simultaneous determination of chlorites and chlorates in samples of water after its disinfection by various oxidants (sodium hypochlorite, ozone, chlorine dioxide).